Effects of Mn addittion, cooling rate and holding temperature on the modification and purification of iron-rich compounds in AlSi10MnMg(Fe) alloy. Issue 2 (February 2023) - Sanchez, Jon Mikel; Arribas, Maribel; Galarraga, Haize; Garcia de Cortazar, Maider; Ellero, Marco; Girot, Franck
Abstract: The use of secondary aluminum alloys in industry is still limited by the high Fe contents in recycled alloys. In general, the Fe-rich intermetallic compounds deteriorate the performance of secondary Al–Si alloys, specially the β-Fe phase. To mitigate the detrimental effects of iron, the influence of diferent cooling rates and holding temperatures on the modification and purification of iron-rich compounds in commercial AlSi10MnMg alloy with 1.1 wt % Fe was studied. According to the results obtained by CALPHAD calculations, the alloy was modified by adding a 0.7 wt%, 1.2 wt%. and 2.0 wt% of Mn. The phase formation and morphology of iron-rich compounds was systematically studied and correlated by different microstructural characterization techniques. The experimental results showed that the detrimental β-Fe phase can be avoided by adding at least 1.2 wt % of Mn at the studied cooling rates. Finally, the effect of different holding temperatures in the sedimentation of Fe-rich compounds also was studied. Hence, the gravitational sedimentation experiments at different holding times and temperatures were conducted to validate the feasibility of the methodology in different processing conditions. The experimental results showed a high Fe removal efficiency up to 64% and 61%, after a holding time of 30 min at 600 °C and 670 °C, respectively. The addition of Mn improved the Fe removal efficiency but not gradually, as the best results were obtained in the alloy containing 1.2 wt % Mn.